Preparation method and application of iron-carbon micro-electrolysis material containing copper-based MOFs

CN119612698BActive Publication Date: 2026-10-23LIAONING UNIVERSITY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411778013.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2026-10-23
Estimated Expiration
2044-12-05

AI Technical Summary

Technical Problem

[0004]目前,铁碳微电解技术由于其处理成本低、不需要额外投加药剂等优点,在水处理方面逐渐受到关注,亚硝酸盐在微电解反应中主要通过吸附在活性炭表面得到电子而被还原去除,但普通活性炭对于水中硝酸盐的吸附性能较差,因而限制了亚硝酸盐在微电解反应中的去除效果

Benefits of technology

1、本发明利用废铁矿渣、活性炭粉、废糖蜜、氯化铵制备铁碳微电解材料,用废铁矿渣代替铁粉,用废糖蜜代替淀粉,将污染环境的废弃物充分利用,以废治废,实现固体废弃物的资源再利用,使得制作成本进一步降低,适合于大面积推广。与此同时,用废糖蜜代替淀粉,不仅能增大铁碳材料的孔隙率使污染物与铁碳微电解材料接触面积更大更易被吸附去除,而且能大大增加铁碳微电解材料的紧密性,使材料更紧实不易松散。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119612698B_ABST
    Figure CN119612698B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of material preparation and application, and particularly relates to a preparation method and application of an iron-carbon micro-electrolysis material containing copper-based MOFs. The preparation method of the iron-carbon micro-electrolysis material containing copper-based MOFs is to comprehensively utilize waste iron slag, activated carbon, waste molasses and ammonium chloride, mix them, mix them with water to form microspheres, and calcine the microspheres to obtain the iron-carbon micro-electrolysis material; copper sulfate, sodium ascorbate and 1,2,4-triazole are sequentially added into a methanol aqueous solution, and a Cu-MOF material is obtained through a hydrothermal reaction. By adding the metal catalyst Cu-MOF material in the iron-carbon micro-electrolysis material, the removal rate of nitrous nitrogen in water reaches about 97%, and the application has the advantages of fast conversion rate, strong anti-interference ability, no secondary pollution and the like; and in the preparation process, the raw materials are widely sourced and low in price, the waste iron slag is used to replace iron powder, and the waste molasses is used to replace starch as a binder, so that comprehensive utilization of waste is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of materials preparation and application technology, specifically relating to a method for preparing and applying an iron-carbon microelectrolysis material containing copper-based MOFs. Background Technology

[0002] With the increasing development of the coal industry, the amount of waste slag generated during mining has also increased year by year, causing adverse effects from indiscriminate dumping and forming a major environmental pollution hazard. The rational utilization and timely treatment of waste slag is urgently needed. Meanwhile, the sugarcane industry, a pillar industry in some southern regions of my country, has repeatedly broken annual production records. While bringing huge profits, it also generates a large amount of waste molasses. How to properly utilize this waste molasses has become a major environmental problem for sugar factories. Iron-carbon micro-electrolysis, as an effective and stable wastewater treatment method, aims to remove pollutants from water and has broad application prospects. Traditional iron-carbon micro-electrolysis processes involve mixing and burning iron powder, activated carbon powder, and starch, resulting in high costs, low efficiency, and poor separation effects. Therefore, finding low-cost, simple, environmentally friendly, highly effective, and stable degradation materials has become an important research goal. Replacing iron powder with waste slag and starch with waste molasses not only achieves comprehensive waste utilization but also increases the porosity and compactness of the iron-carbon micro-electrolysis material, which is of practical significance.

[0003] With the improvement of industrial and agricultural production levels, human activities have led to a large amount of nitrogen emissions, including the combustion of fossil fuels, industrial wastewater discharge, excessive use of nitrogen fertilizers in agriculture, and livestock farming. These activities have made inorganic nitrogen compounds a ubiquitous water pollutant globally. Nitrogen pollution has become a major global water pollution problem, adversely affecting the natural environment and human health. High concentrations of nitrates and nitrites, once ingested, have carcinogenic and other negative effects, potentially leading to methemoglobinemia, stomach cancer, and metabolic disorders. Nitrites (NO2) - Nitrite is an important intermediate in the nitrogen (N) cycle and can accumulate in anaerobic environments through denitrification, leading to public health problems. It can also contribute to the emission of potentially reactive nitrogen oxides into the atmosphere, such as nitrite (HONO), nitric oxide (NO), and nitrous oxide (N2O), the latter being a major greenhouse gas. According to the U.S. Environmental Protection Agency's (USEPA) standards for the lowest levels of maximum contaminants in drinking water, nitrite is more toxic than nitrate, making the control and removal of nitrite from water sources of great importance.

[0004] Currently, iron-carbon microelectrolysis technology is gaining increasing attention in water treatment due to its advantages such as low treatment cost and no need for additional reagents. Nitrite is mainly removed in microelectrolysis by gaining electrons through adsorption on the surface of activated carbon. However, ordinary activated carbon has poor adsorption performance for nitrates in water, thus limiting the removal efficiency of nitrite in microelectrolysis. This study uses waste slag and ordinary activated carbon as raw materials to construct a microelectrolysis system. Waste molasses was added to make the iron-carbon microelectrolysis material less prone to disintegration, thus preparing an iron-carbon microelectrolysis material. Furthermore, the removal efficiency of dissolved nitrite in water was further improved by doping with Cu-based MOFs. Summary of the Invention

[0005] The technical problem to be solved by this invention is to provide a method for preparing a novel iron-carbon micro-electrolysis material doped with copper-based MOFs and its application in removing nitrite from water. This invention reduces the cost of iron-carbon micro-electrolysis treatment by comprehensively utilizing waste iron slag and waste molasses to treat waste. At the same time, the iron-carbon micro-electrolysis material doped with copper-based MOFs prepared by this invention can greatly improve the adsorption and removal of nitrite nitrogen in water and has good recyclability in the water treatment process.

[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows: A method for preparing an iron-carbon microelectrolysis material containing copper-based MOFs includes the following steps: 1) Mixing: Add waste iron slag, activated carbon, waste molasses, and ammonium chloride to a mixer and mix evenly to obtain a mixture; 2) Forming microspheres: Add distilled water to the mixture and continue stirring until the mixture and water form a cohesive solid, producing 3-5g microspheres; 3) Drying: After drying the microspheres in a drying oven at 70-90℃ for 6 hours, place them in a crucible and calcine them in a tube furnace. After naturally cooling to room temperature, grind them to 100 mesh to obtain the iron-carbon microelectrolysis material. 4) Catalyst preparation: Copper sulfate, sodium ascorbate, and 1,2,4-triazole were added to a methanol aqueous solution, stirred evenly, heated in a high-pressure reactor, cooled to room temperature, filtered, and freeze-dried to obtain Cu-MOFs powder. 5) The Cu-MOFs powder was uniformly incorporated into the iron-carbon microelectrolysis material to obtain the iron-carbon microelectrolysis material containing copper-based MOFs.

[0007] Furthermore, in the above preparation method, in step 1), the mass ratio of waste iron slag, activated carbon, and waste molasses is 5:2:2.

[0008] Furthermore, in the above preparation method, step 3), the calcination conditions are as follows: the protective gas is nitrogen, the flow rate of the protective gas is 30~50mL / min; the temperature is raised from room temperature to 400~550℃, held for 1~3h, then raised to 900℃, held for 2~3h, and the heating rate is 5~8℃ / min.

[0009] Furthermore, in the above preparation method, in step 4), the mass ratio of copper sulfate, sodium ascorbate, and 1,2,4-triazole is 5:6:1.

[0010] Furthermore, in the above preparation method, step 4), the heating conditions are: heating at 900℃ for 9-10 hours.

[0011] Furthermore, in the above preparation method, step 5), the doping ratio of the iron-carbon microelectrolysis material to Cu-MOFs is 10~100:1.

[0012] Application of copper-based MOFs-containing iron-carbon microelectrolysis materials prepared by any of the above methods in the treatment of nitrite nitrogen in wastewater.

[0013] Further, the above application is carried out as follows: iron-carbon microelectrolysis material containing copper-based MOFs is added to wastewater containing nitrite nitrogen, and the reaction is carried out under anaerobic conditions in a closed environment with stirring at room temperature. Solid-liquid separation is achieved using a 0.45um filter membrane, and the resulting supernatant is the treated effluent.

[0014] Furthermore, in the above applications, the dosage of the iron-carbon microelectrolysis material containing copper-based MOFs is 5~30 g / L.

[0015] Furthermore, in the above application, the stirring time is 0~120min.

[0016] The present invention has the following beneficial effects: 1. This invention utilizes waste iron slag, activated carbon powder, waste molasses, and ammonium chloride to prepare iron-carbon micro-electrolysis materials. By replacing iron powder with waste iron slag and starch with waste molasses, it fully utilizes environmentally polluting waste, treating waste with waste, and achieving resource reuse of solid waste. This further reduces production costs and makes it suitable for large-scale promotion. Simultaneously, replacing starch with waste molasses not only increases the porosity of the iron-carbon material, allowing for a larger contact area between pollutants and the iron-carbon micro-electrolysis material, making them easier to adsorb and remove, but also significantly increases the compactness of the iron-carbon micro-electrolysis material, making it more compact and less prone to loosening.

[0017] 2. Based on iron-carbon microelectrolysis materials, this invention utilizes a hydrothermal method to prepare Cu-MOFs using copper sulfate, 1,2,4-triazole, and sodium ascorbate. The doping of Cu-MOFs further enhances the electron transfer rate in solution, stimulating the iron-carbon microelectrolysis materials to react at a faster rate, thus providing more electrons. The electrons adsorbed at the active sites on the Cu-MOFs surface promote the further conversion of nitrite nitrogen into ammonia nitrogen and nitrogen gas, significantly improving the removal efficiency of nitrite nitrogen. Attached Figure Description

[0018] Figure 1 The image shows the SEM characterization spectrum of the iron-carbon microelectrolysis material.

[0019] Figure 2 The image shows the XRD characterization spectrum of the iron-carbon microelectrolysis material containing copper-based MOFs.

[0020] Figure 3 The graph shows the changes in nitrogen concentration in the effluent after treatment with different dosages of iron-carbon microelectrolysis materials containing copper-based MOFs.

[0021] Figure 4 The graph shows the variation of nitrogen concentration in the effluent after treatment with different iron-carbon microelectrolysis materials containing copper-based MOFs.

[0022] Figure 5 This is a graph showing the changes in nitrogen concentration in the effluent after treatment with iron-carbon microelectrolysis materials containing copper-based MOFs for different treatment times. Detailed Implementation

[0023] The technical solution of the present invention will be clearly and completely described below with reference to specific embodiments, so as to better understand the technical solution. The scope of protection of the present invention is not limited to the following embodiments.

[0024] Example 1: Preparation of iron-carbon microelectrolysis materials containing copper-based MOFs

[0025] (a) Preparation of packing material: 1) Mixing: Taking a total weight of 10g as an example, add 5g of waste iron slag, 2g of activated carbon, 2g of waste molasses, and 1g of ammonium chloride to a mixer and mix evenly to obtain a mixture. 2) Forming microspheres: Add distilled water to the mixture and continue stirring until the mixture and water form a cohesive solid, producing 3-5g microspheres; 3) Drying: After drying the microspheres in a drying oven at 80℃ for 6 hours, place them in a crucible and calcine them in a tube furnace (nitrogen flow rate is 45 mL / min; temperature is increased from room temperature to 550℃, held for 1 hour, then increased to 900℃, held for 2 hours, with a heating rate of 7℃ / min). After naturally cooling to room temperature, grind them to 100 mesh to obtain the iron-carbon microelectrolysis material (Fe / C). (II) Catalyst Preparation: 4) Copper sulfate, sodium ascorbate, and 1,2,4-triazole were added to a methanol aqueous solution in a ratio of 5:6:1. After stirring evenly, the mixture was heated at 900°C for 10 hours in a high-pressure reactor. After cooling to room temperature, the mixture was filtered and freeze-dried to obtain copper-based MOF powder (Cu-MOFs). (III) Preparation of iron-carbon microelectrolysis materials containing copper-based MOFs: 5) Cu-MOFs powder was uniformly doped into the iron-carbon microelectrolysis material. By changing the amount of Cu-MOFs added, iron-carbon microelectrolysis materials containing copper-based MOFs (Fe / C-Cu-MOFs) with Cu-MOFs doping amounts of 1%, 1.5%, 2%, 2.5%, 5%, 7.5%, and 10% were obtained respectively.

[0026] Figure 1 The following are SEM characterization spectra of iron-carbon microelectrolysis materials containing copper-based MOFs, such as... Figure 1 As shown, the average particle size of the iron-carbon microelectrolysis material containing Cu-based MOFs is 4901.03 μm. After doping, some columnar particles can be clearly seen on the surface of the iron-carbon microelectrolysis material, making its surface uneven and rough, which greatly increases the contact area between the water sample and the microelectrolysis material and improves the treatment effect.

[0027] Figure 2 The XRD characterization spectra of iron-carbon microelectrolysis materials containing copper-based MOFs are shown below. Figure 2 As shown, the iron-carbon microelectrolysis material containing Cu-based MOFs exhibits a distinct characteristic peak at 2θ, consistent with PDF#43-1815 and PDF#21-1602 cards, indicating that activated carbon reduces waste iron ore to zero-valent iron with a central cubic structure and fully binds and supports it. Simultaneously, distinct characteristic peaks are observed, consistent with PDF#06-0696 and PDF#17-0333, indicating that the copper-based catalyst doped in the iron-carbon microelectrolysis material is a MOF structure catalyst formed by coordination bonds between copper and organic ligands.

[0028] Example 2 Application

[0029] Experimental water sample: NaNO2 solution with a nitrite nitrogen content of 40 mg / L.

[0030] Analysis and testing methods: The testing methods in this experiment strictly followed the standard methods in "Methods for Monitoring and Analysis of Water and Wastewater". The specific test indicators and methods are as follows: Nitrate Nitrogen: Determination of Nitrate Nitrogen in Water by Ultraviolet Spectrophotometry (Trial) HJ / T 346-2007; Nitrite nitrogen: Determination of nitrite nitrogen in water quality by spectrophotometry GB 7493-87; Ammonia nitrogen: Determination of ammonia nitrogen in water quality using Nessler's reagent spectrophotometric method HJ 535-2009.

[0031] (I) Comparison of the effects of Cu-MOFs doping on nitrite treatment in iron-carbon microelectrolysis materials: To investigate the effects of Cu-MOFs doping on nitrite treatment, 2.5 g of (1) iron-carbon microelectrolysis material (Cu-MOFs doping amount of 0%) and 2.5 g of iron-carbon microelectrolysis material containing copper-based MOFs (Cu-MOFs doping amount of 2%) were added to 100 mL of experimental water samples. The reaction was carried out under anaerobic conditions in a closed environment and stirred at room temperature for 2 h. Samples were taken and filtered through a 0.45 μm filter membrane. The NO3 content of the supernatant was then measured. - -N, NO2 - -N, NH4 + -N content.

[0032] Experimental results: Table 1. Changes in inorganic nitrogen content in water before and after microelectrolysis treatment. Water sample before treatment 40.000 0.000 0.000 0.000 Water sample after Fe / C-Cu-MOFs treatment 0.853 19.561 19.573 97.849 Fe / C treated water sample 5.840 10.712 23.439 85.430 As shown in Table 1, the nitrate content was extremely low during the experiment, almost negligible compared to the content of other nitrogen elements.

[0033] Fe / C-Cu-MOFs are more effective than Fe / C in removing nitrite nitrogen. Fe / C-Cu-MOFs can also remove NO2. - -N content decreased from 40.000 mg / L to 0.853 mg / L, with a removal rate of 97.849%. Fe / C reduced NO2 content. - -N content decreased from 40 mg / L to 5.840 mg / L, with a removal rate of 85.430%. Therefore, compared to Fe / C, Fe / C-Cu-MOFs can improve NO2 removal. - -N removal rate.

[0034] (II) Comparison of dosage of iron-carbon microelectrolysis materials containing copper-based MOFs: Experimental water samples were treated using iron-carbon microelectrolysis materials containing copper-based MOFs. The treatment process was controlled to investigate the effluent effects of different Fe / C-Cu-MOFs dosages. The dosages were 5 g / L, 10 g / L, 15 g / L, 20 g / L, 25 g / L, and 30 g / L. The reaction was carried out under anaerobic conditions in a closed environment with stirring at room temperature for 1 h. The degradation effect of nitrite in the effluent and the optimal total dosage were compared.

[0035] The reduction of NO2 by a galvanic cell system composed of Fe / C-Cu-MOFs - -N produces NH4 + -N and N2, since nitrogen in the experimental water exists in the form of inorganic compounds, can be used to treat NO2. - -N and NH4 + -N is used in nitrogen balance calculations to reflect the selectivity of nitrite to nitrogen gas conversion; in the following text, NO2 will be used. - -N and NH4 + The difference between the total -N content and the initial content indicates the corresponding nitrogen conversion rate.

[0036] Depend on Figure 3 It can be seen that as the dosage of Fe / C-Cu-MOFs increases from 0 g / L to 25 g / L, NO2... - The NO2- content decreased from 40 mg / L to 8.585 mg / L, and the removal rate increased from 0 to 79.628%; however, when the dosage increased from 25 g / L to 30 g / L, the removal rate only increased from 79.63% to 83.610%. - The removal rate of -N changed relatively slowly. Meanwhile, as the dosage of Fe / C-Cu-MOFs increased from 0 g / L to 30 g / L, the concentration of N2 also increased continuously, from 0 to 26.030 mg / L. Therefore, based on the above data, a dosage of 25 g / L is the optimal reaction condition.

[0037] (III) Comparison of doping content in iron-carbon microelectrolysis materials containing copper-based MOFs: Water samples containing nitrite were treated using iron-carbon microelectrolysis materials containing copper-based MOFs. The treatment process was controlled to investigate the effluent degradation effect of different Cu-MOF doping amounts within the Fe / C-Cu-MOFs material. Doping ratios were 0%, 1%, 1.5%, 2%, 2.5%, 5%, 7.5%, and 10%. The reaction was carried out under anaerobic conditions in a closed environment with stirring at room temperature for 1 hour. The degradation effect of nitrite in the effluent and the optimal dosage were compared.

[0038] Depend on Figure 4 It can be seen that as the Cu-MOFs doping ratio increases from 0% to 2%, NO2 -The NO2 content decreased from 40 mg / L to 4.258 mg / L, and the removal rate increased from 0 to 89.170%. This occurred as the Cu-MOF doping ratio increased from 2% to 10%. - The N₂ concentration increased from 4.26 mg / L to 9.78 mg / L, while the removal rate decreased from 89.17% to 75.15%. Simultaneously, as the Cu-MOF doping ratio increased from 0% to 10%, the N₂ concentration also increased from 0 to 26.189 mg / L. Therefore, a Cu-MOF doping ratio of 2% represents the optimal reaction condition.

[0039] (iv) Comparison of processing times for iron-carbon microelectrolysis materials containing copper-based MOFs: Water samples containing nitrite were treated using iron-carbon microelectrolysis materials containing copper-based MOFs. The treatment process was controlled to investigate the effluent effect of Fe / C-Cu-MOFs treatment for different treatment times. The reaction was carried out under anaerobic conditions in a closed environment with stirring times of 0, 15, 30, 60, 90, and 120 min at room temperature. The degradation effect of nitrite in the effluent and the optimal treatment time were compared.

[0040] Depend on Figure 5 It can be seen that as the processing time is increased from 0 min to 90 min, NO2 - The NO2 content decreased from 40 mg / L to 1.181 mg / L, and the removal rate increased from 0 to 97.022%. During the process of extending the treatment time from 90 min to 120 min, NO2... - The N2 concentration decreased slowly, from 1.18 mg / L to 0.85 mg / L, while the removal rate increased from 97.022% to 97.849%. Simultaneously, as the treatment time increased from 0 min to 120 min, the N2 concentration also increased continuously, from 0 to 29.577 mg / L. Therefore, a treatment time of 90 min is the optimal reaction condition.

[0041] In summary, the treatment of NO2 by Fe / C-Cu-MOFs... - The optimal treatment conditions for sodium nitrate water samples with a -N content of 40 mg / L are: dosage of 25 g / L, Cu-MOFs doping ratio of 2%, and treatment time of 90 min.

Claims

1. The application of an iron-carbon microelectrolysis material containing copper-based MOFs in the treatment of nitrite nitrogen in wastewater, characterized in that, The method is as follows: Add the iron-carbon microelectrolysis material containing copper-based MOFs to the wastewater containing nitrite nitrogen, and react in a closed manner under anaerobic conditions with stirring at room temperature. Solid-liquid separation is achieved using a 0.45μm filter membrane, and the resulting supernatant is the treated effluent. The preparation method of the iron-carbon microelectrolysis material containing copper-based MOFs includes the following steps: 1) Mixing: Add waste iron slag, activated carbon, waste molasses, and ammonium chloride to a mixer and mix evenly to obtain a mixture; 2) Forming microspheres: Add distilled water to the mixture and continue stirring until the mixture and water form a cohesive solid, producing 3-5g microspheres; 3) Drying: After drying the microspheres in a drying oven at 70-90℃ for 6 hours, place them in a crucible and calcine them in a tube furnace. After naturally cooling to room temperature, grind them to 100 mesh to obtain the iron-carbon microelectrolysis material. 4) Catalyst preparation: Copper sulfate, sodium ascorbate, and 1,2,4-triazole were added to a methanol aqueous solution, stirred evenly, heated in a high-pressure reactor, cooled to room temperature, filtered, and freeze-dried to obtain Cu-MOFs powder. 5) The Cu-MOFs powder was uniformly incorporated into the iron-carbon microelectrolysis material to obtain the iron-carbon microelectrolysis material containing copper-based MOFs.

2. The application according to claim 1, characterized in that, In step 1), the mass ratio of waste iron slag, activated carbon, and waste molasses is 5:2:

2.

3. The application according to claim 1, characterized in that, In step 3), the calcination conditions are as follows: the protective gas is nitrogen, the flow rate of the protective gas is 30~50mL / min; the temperature is raised from room temperature to 400~550℃, held for 1~3h, then raised to 900℃, held for 2~3h, and the heating rate is 5~8℃ / min.

4. The application according to claim 1, characterized in that, In step 4), the mass ratio of copper sulfate, sodium ascorbate, and 1,2,4-triazole is 5:6:

1.

5. The application according to claim 1, characterized in that, In step 5), the doping ratio of the iron-carbon microelectrolysis material to Cu-MOFs is 10~100:

1.

6. The application according to claim 1, characterized in that, The dosage of the iron-carbon microelectrolysis material containing copper-based MOFs is 5~30 g / L.

7. The application according to claim 1, characterized in that, The stirring time is 0~120 min.

Citation Information

Patent Citations

  • Method for producing regularized iron-carbon micro-electrolysis filler from high iron-copper slag

    CN106277225A